Socio-economic inequalities in arts engagement and depression among older adults in the United Kingdom: evidence from the English Longitudinal Study of Ageing. (September 2021) - Shaikh, Mujaheed; Tymoszuk, Urszula; Williamon, Aaron; Miraldo, Marisa
Abstract: Objectives: Arts engagement has been positively linked with mental health and well-being; however, socio-economic inequalities may be prevalent in access to and uptake of arts engagement reflecting on inequalities in mental health. This study estimated socio-economic inequality and horizontal inequity (unfair inequality) in arts engagement and depression symptoms of older adults in England. Trends in inequality and inequity were measured over a period of ten years. Study design: This is a repeated cross-sectional study. Methods: In this analysis, we used data from six waves (waves 2 to 7) of the nationally representative English Longitudinal Study of Ageing. We estimated socio-economic inequality using concentration curves that plot the distribution of arts engagement and depression symptoms against the distribution of wealth. A concentration index was used to measure the magnitude of the inequality. Unfair inequality was then calculated for need-standardised arts engagement using a horizontal inequity index (HII). Results: The study sample included adults aged 50 years and older from waves 2 (2004/2005, n = 6620) to 7 (2014/2015, n = 3329). Engagement with cinema, galleries and theatre was pro-rich unequal, i.e. concentrated among the wealthier, but inequality in depression was pro-poor unequal, i.e. concentrated more among the less wealthy. While pro-rich inequality in arts engagement decreased from wave 2 (conc. index: 0·291, 95% confidence interval 0·27 to 0·31) to wave 7 (conc. index: 0·275, 95% confidence interval 0·24 to 0·30), pro-poor inequality in depression increased from wave 2 (conc. index: −0·164, 95% confidence interval -0·18 to −0·14) to wave 7 (conc. index: −0·189, 95% confidence interval -0·21 to −0·16). Depression-standardised arts engagement showed horizontal inequity that increased from wave 2 (HII: 0·455, 95% confidence interval 0·42 to 0·48) to wave 7 (HII: 0·464, 95% confidence interval 0·42 to 0·50). Conclusions: Our findings suggest that while socio-economic inequality in arts engagement might appear to have reduced over time, once arts engagement is standardised for need, inequality has actually worsened over time and can be interpreted as inequitable (unfair). Relying on need-unstandardised estimates of inequality might thus provide a false sense of achievement to policy makers and lead to improper social prescribing interventions being emplaced.